Redistributive effects of government programmes : the Chilean case - Foxley, Alejandro; Aninat, Eduardo; Arellano, José Pablo; International Labour Office (Oxford ; New York : Pergamon Press, 1979)
This book deals with the low levels of per capital income in economies and it unequal distribution that are conducive to greater dissatisfaction with the functioning of the economy system in the societies
A study prepared for the International Labour Office within the framework of the World Employment Programme.
Includes bibliographical references and index.
oo 10/10/2018
Loans
Keywords: Income distribution; Taxation; Government spending policy; Social security